Manfaat Penerapan Sistem Informasi Akuntansi terhadap Kinerja Karyawan dengan Pendekatan TAM (Studi Fenomenologi terhadap Penggunaan Sistem Informasi Akuntansi di PT PLN UP3 Demak) - Astari Nuriadini; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2022)
This study entitled "The Benefits of Implementing Accounting Information Systems on Employee Performance at PT PLN UP3 Demak with the TAM Approach". The purpose of this study was to identify and analyze the benefits of implementing an accounting information system on employee performance using the TAM model approach. This research method uses a phenomenological approach. This research was conducted using a qualitative method with a phenomenological approach. The data was obtained by using a questionnaire survey technique which was distributed to 37 employees of PT PLN UP3 Demak who used the accounting information system as participants. Data analysis using the TAM model approach is related to perceived usefulness, perceived ease of use and attitude of use with employee performance.The results of the study indicate that the application of an accounting information system provides benefits to employee performance with the TAM model approach.